Pelayanan Publik pada Pusat Kesehatan Masyarakat Kecamatan Marpoyan Damai Pekanbaru Tahun 2013 - Wan Asrida; Rafni Pohan (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2014)
Public Services of Public Health Centers at the Sub District Marpoyan Damai in the City of Pekanbaru year 2013-2014. Purpose of this study was to determine the Public Services in Public Health Centers at the District Marpoyan Damai in City of Pekanbaru and what are the factors that obstruct the services. This research used qualitative methods, research that provides an explanation of data is done through the process of preparation, presentation of data, observation, interview techniques, and Documentation. The result of this research. concluded that the Public Service is still not optimal given employee health centers. Can be seen from the standard indicators of public services according to kepmenpan No. 63 of 2003, service procedures are difficult, long turnaround time of service, limited service products, facilities and infrastructure is not yet complete, and then the employee competence of Health Centre, who do not show a friendly attitude to patients.